Simulation of operating conditions for syngas production from municipal solid waste and carbon footprint assessment - Chia, Peiwen (Nanyang Technological University, 2023)
With the rapidly growing demand for energy with the significant rise in the quantity of municipal waste generated (MSW), the management of MSW has become very crucial. Gasification, a thermochemical waste management technology, has the potential to reduce volume and mass of MSW while recovering materials and energy through the process. Hence this study investigates the operating conditions for syngas production from municipal solid waste through simulation modelling and carbon footprint assessment. This method utilizes ASPEN Plus software to create and simulate the gasification process of MSW under different operating parameters. The ASPEN Plus model was built and validated using literature sources. Additionally, to determine the carbon footprint of the gasification process under varying operating parameters, GaBi software is used to simulate the CO2e emissions of these parameters. The results obtained reveal that (1) the increase in temperature leads to an increase in production of CO and H2 gases, and decrease in CO2 gas, (2) CO2 gas increases and CO and H2 gases decrease as oxygen-enriched air gasification agent is increased, (3) an increase in the steam gasification agent causes an increase in the H2 and CO2 gases while decreasing the CO gas.